فعالية الاتصال الإداري في المؤسسة الصناعية - قبقوب, الدكتور : عيسى،; برويس, الأستاذة: وردة (Sciences de l'Homme et de la Société; Vol. 15 (2015): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ(Juin), 2015)
الملخص: يهدف هذا المقال إلى دراسة فعالية الاتصال الإداري في المؤسسة الصناعية باعتبار أن الاتصالات الإدارية نظام يتعلق بالمؤسسات، وبدون وجود هذه الأنظمة الخاصة بالاتصالات تفقد المؤسسات القدرة على العمل وانجازاته، حيث أن أنظمة الاتصالات الإدارية تزود الممارسين بالإجراءات، والخطوات، والنماذج، والإرشادات الخاصة بممارسة الأنواع المختلفة للاتصالات مثل: (التقارير، والرسائل، والمذكرات، والاجتماعات).   Abstract :             This article aims to study the effectiveness of the administrative contact in Industrial Corporation as the system of communication in regard to the institutions, and without the existence of these regulations relating to communications the institutions lose its ability to work and achievements. The administrative communication systems provide practitioners with steps, forms, and instructions for the exercise of the different types Communications such as: (reports, letters, memos, meetings).